When Children Research Researchers (2011)
At EAFIT Children's University, activities have been nurtured by two types of initiatives: those that lead children to research and those that allow them to interact directly with researchers. In Meetings Questions, the first stage of the program, children between 7 and 13 share their thoughts and feelings with a researcher based on a question that brings them together. In Expeditions to Knowledge, the second stage, they propose projects to investigate their topics of interest.